Cryptocurrency Volatility and Risk Management Strategies in Emerging Financial Markets - PA Andiena Nindya Putri; Delfian Zaman; Muhammad Sujai; M. Joni; Fitriningsih Amalo (DINASTI RESEARCH, 2026)
This study examines cryptocurrency volatility and evaluates risk management strategies within emerging financial markets using a systematic literature review approach. Cryptocurrencies have gained significant attention as alternative financial assets; however, their extreme price volatility presents substantial risks, particularly in markets characterized by weak institutional frameworks and limited financial literacy. This research synthesizes findings from 45 scholarly sources published between 2008 and 2025, focusing on the determinants of volatility, market characteristics in emerging economies, and the effectiveness of various risk management approaches. The results indicate that cryptocurrency volatility is primarily driven by speculative trading, investor sentiment, regulatory uncertainty, and macroeconomic shocks. These factors are further amplified in emerging markets due to structural limitations such as underdeveloped regulations, low institutional participation, and unstable capital flows. In terms of risk management, strategies such as hedging and GARCH-based volatility modeling are found to be more effective compared to traditional methods like diversification and Value-at-Risk, which show limited reliability under extreme market conditions. The study also highlights the significant role of behavioral and regulatory factors in influencing market stability. Furthermore, a critical research gap is identified, namely the limited focus on emerging financial markets in existing literature. The findings suggest the need for context-specific risk management frameworks, improved regulatory policies, and enhanced financial literacy to support sustainable cryptocurrency adoption.